Role of the Azotobacter vinelandii Nitrogenase-Protective Shethna Protein in Preventing Oxygen-Mediated Cell Death - Maier, R. J. (American Society for Microbiology, 2000)
Azotobacter vinelandii strains lacking the nitrogenase-protective Shethna protein lost viability upon carbon-substrate deprivation in the presence of oxygen. This viability loss was dependent upon the N(2)-fixing status of cultures (N(2)-fixing cells lost viability, while non-N(2)-fixing cells did not) and on the ambient O(2) level. Supra-atmosheric O(2) tensions (40% partial pressure) decreased the viable cell number of the mutant further, and the mutant had a slightly higher spontaneous mutation frequency than the wild type in the high-O(2) conditions. Iron starvation conditions, which resulted in fourfold-reduced superoxide dismutase levels, were also highly detrimental to the viability of the protective protein mutants, but these conditions did not affect the viability of the wild-type strain. Nitrogenase or other powerful reductants associated with N(2) fixation may be sources of damaging partially reduced oxygen species, and the production of such species are perhaps minimized by the Shethna protein.